Predicting recurrence of non-muscle invasive bladder urothelial carcinoma: predictive value of the optimal cut-off value of Ki67 - Peng, Rende; Zhang, Yaoyu; Jia, Mingzhu; Yi, Xinping; Yi, Xiaoyao; Li, Shadan; Pi, Jiangchuan; Meng, Wenjun (Frontiers in Oncology, 2025)
ObjectiveTo investigate the optimal cut-off value of immunohistochemical marker Ki67 as a prognostic factor to predict the recurrence of non-muscle invasive bladder urothelial carcinoma (NMIBUC).MethodsA total of 331 patients diagnosed with NMIBUC who underwent surgery in the Yongchuan Hospital and the Second Affiliated Hospital of Chongqing Medical University from January 2012 to January 2020 were finally included in this study. The optimal cut-off value of Ki67 for predicting recurrence of NMIBUC was calculated by ROC curve and Youden index. According to the cut-off value, the patients were divided into high ratio group and low ratio group, and the clinicopathological data of the two groups were compared. Univariate and multivariate regression analysis were used to analyze the relationship between the expression of Ki67 and postoperative recurrence of NMIBUC. The Kaplan-Meier curve was used for survival analysis.Results18% is the optimal cut-off value of Ki67 for predicting postoperative recurrence of NMIBUC. High Ki67 expression (Ki67>18%) was significantly correlated with tumor stage (P=0.001), tumor grade (P=0.014), immediate postoperative instillation (P=0.001), the expression of P53 (P=0.019) and CK20 (P=0.001). Ki67 expression greater than 18% was an independent risk factor for high recurrence rate of NMIBUC (P=0.001). Moreover, the 1-year and 3-year recurrence-free survival (RFS) of the high Ki67 group were 56.6% (95%CI 51.2%-62%) and 43.6% (95%CI 37.5%-49.7%) respectively, which were significantly lower than those in low Ki67 group which present as 92.9% (95%CI 89.0%-96.8%) and 88.3% (95%CI 82.4%-94.2%) respectively, and the difference was statistically significant (P<0.001).Conclusions18% is the optimal cut-off value of Ki67 for predicting recurrence of NMIBUC. Ki67>18% is an independent risk factor for high recurrence rate of NMIBUC. This cut-off value can more accurately predict the risk of recurrence and has the potential clinical value for guiding the postoperative adjuvant treatment and follow-up strategy of NMIBUC.